Big trees burning: divergent wildfire effects on large trees in open- vs. closed-canopy forests - Meigs, Garrett W., author; Chamberlain, Caden P., author; Begley, James S., author; Cansler, C. Alina, author; Churchill, Derek J., author; Cova, Gina R., author; Donato, Daniel C., author; Halofsky, Joshua S., author; Kane, Jonathan T., author; Kane, Van R., author; Prichard, Susan J., author; Smith, L. Annie C., author; et al. (Colorado State University. Libraries, 2025)
Wildfire activity has accelerated with climate change, sparking concerns about uncharacteristic impacts on mature and old-growth forests containing large trees. Recent assessments have documented fire-induced losses of large-tree habitats in the US Pacific Northwest, but key uncertainties remain regarding contemporary versus historical fire effects in different forest composition types, specific impacts on large trees within closed versus open canopies, and the role of fuel reduction treatments. Focusing on the 2021 Schneider Springs Fire, which encompassed 43,000 ha in the eastern Cascade Range of Washington and burned during a period of severe drought, this study addresses three interrelated questions: (1) Are burn severity distributions consistent with historical fire regimes in dry, moist, and cold forest types? (2) How does burn severity vary among forest structure classes, particularly large trees with open versus closed canopies? (3) How do fuel reduction treatments influence forest structure and burn severity inside and outside of treated areas? Within each forest type, burn severity proportions were similar to historical estimates, with lower overall severity in dry forests than in moist and cold forests. However, across all forest types combined, high-severity fire affected 30% (4500 ha) of large-tree locations with tree diameters >50 cm. In each forest type, burn severity was lower in locations with large-open structure (<50% canopy cover) than in locations with large-closed structure (>50% canopy cover). Burn severity also was lower inside than outside treated sites in all structure classes, and untreated large-closed forests tended to burn at lower severity closer to treatments. These results highlight the susceptibility of dense, late-successional forests to contemporary fires, even in events with widespread potentially beneficial effects consistent with historical fire regimes. These results also illustrate the effectiveness of treatments that shift large-closed to large-open structures and suggest that treatments may help mitigate fire effects in adjacent large-closed forests. Long-term monitoring and adaptive management will be essential for conserving critical wildlife habitats and fostering ecosystem resilience to climate change, wildfires, and other disturbances.
Keywords: adaptive management; burn severity; forest composition and structure; fuel reduction treatments; large trees; late-successional habitat; mature and old-growth forests; wildfire